Review of chest CT manifestations of COVID-19 infection. (2020) - El Homsi, Maria; Chung, Michael; Bernheim, Adam; Jacobi, Adam; King, Michael J.; Lewis, Sara; Taouli, Bachir
Highlights: RT-PCR, the standard of reference for diagnosis, has variable sensitivity of 32%–93%. Bilateral peripheral ground-glass opacities are the main chest CT features of COVID-19 pneumonia. CT has excellent sensitivity but limited specificity for diagnosing COVID-19 pneumonia. Chest CT is not recommended for screening of COVID-19 infection. Abstract: Coronavirus disease-19 (COVID-19) is a viral pandemic that started in China and has rapidly expanded worldwide. Typical clinical manifestations include fever, cough and dyspnea after an incubation period of 2–14 days. The diagnosis is based on RT-PCR test through a nasopharyngeal swab. Because of the pulmonary tropism of the virus, pneumonia is often encountered in symptomatic patients. Here, we review the pertinent clinical findings and the current published data describing chest CT findings in COVID-19 pneumonia, the diagnostic performance of CT for diagnosis, including differential diagnosis, as well the evolving role of imaging in this disease.